PENGOLAHAN AIR MINUM SUMUR GALI UNTUK RUMAH TANGGA SECARA AERASI, FILTRASI DAN DESINFEKSI - Ganefati, Sri Puji (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Water is the main needed for human being. The increasing effort of general health and healthy life-environment is influenced by quality and quantity of water. Therefore, we need to process water with some methods. In fact, the ADKL (Analisis dampak kesehatan lingkungan / environmental health impact analysis) study held in 2001, indicate that water quality from dig-well in Moyudan, Sleman, Yogyakarta, was below the standard of pure-water quality. It is important to complete the pure-water needed from dig-well with simple model processing from local resources by apropriate technologies in order to increase the water quality in household. Structureof the process, consist of : aeration that principally give chemical oxidation, filtration for filtering dirty material and disinfection for killing the microbes.The aim for this research was to understand the increasing of water quality from dig-well in Sumbersari, moyudan, sleman, yogyakarta on parameter of E. coli, nitrite, nitrate and sulphate, after processed by aeration, filteration and disinfection model with variation of debit : 1, 2 and 3 liter/minute. The research was experimental type with pre-test and post-test group design. Location of the research was in Sumbersari village, moyudan, sleman, yogyakarta. The independent variable was dig-well processing using aeration, filtration and disinfection model with variation of debit, while, the dependent variable were the decreasing/increasing of E coli, Nitrite, nitrate and sulphate. The result showed that after processed, E coli and nitrite was decreased, while Nitrate and sulphate was increased. Value of the parameter was below the standard. We suggest that, people of sumbersari vilage, Moyudan, Sleman, Yogyakarta, use the simple dig-well processing to improve the water quality of their dig-well.